ANTHROPOLOGICAL CONTRIBUTION TO UNDERSTANDING ТHE POSITION OF THE FAMILIES OF MISSING SERBS IN KOSOVO AND METOHIJA (Heritage, 2022)
This paper approaches the topic of missing Serbs in Kosovo and Metohija by the application of the anthropological theoretical framework on waiting, which treats this waiting process as socially and politically constructed. Furthermore, it considers the role of the families of missing persons in memory praxis related to this humanitarian problem, and also illuminates some of the existential problems that they are facing. By outlining the relevance of understanding the position of families of missing persons, it was shown that their personal stories contribute to the formation of a collective narrative, which is important to the wider community of displaced Serbs from Kosovo and Metohija. Additionally, it was concluded that the ability of this humanitarian problem to contribute to the conflict resolution, depends not only on the investigation of missing people, but also on a wider recognition of victims and the protection of their family members and organizations formed by them, which carry on the duties of establishing interethnic cooperation. The misuse of this humanitarian problem, as outlined by their families, is shown as a serious impediment to mending interethnic relations and an important concern that calls for wider attention. The paper tries to give a closer look at the voices and silences of families of missing persons by showing how their waiting for investigation and information regarding the disappearances is politically structured, and at the same time charged with the promise of social change
Keywords: Kosovo and Metohija, missing persons, abductions, Serbs, chronic waiting, conflict, internally displaced persons, narrative